Noise annoyance and risk of prevalent and incident atrial fibrillation–A sex-specific analysis - Hahad, Omar; Beutel, Manfred E.; Gilan, Donya A.; Chalabi, Julian; Schuster, Alexander K.; Gianicolo, Emilio; Lackner, Karl J.; Lieb, Klaus; Galle, Peter R.; Wild, Philipp S.; Daiber, Andreas; Münzel, Thomas (Frontiers in Public Health, 2022)
Background: While chronic exposure to high levels of noise was demonstrated to increase the risk of various cardiovascular disease, the association between noise annoyance and risk of cardiovascular disease remains still inconsistent. Recently, we showed that noise annoyance is associated with prevalent atrial fibrillation in the general population. However, the association between noise annoyance and risk of incident atrial fibrillation as well as potential sex-differences remain still elusive. Methods and Results: 15,010 subjects from a German population-based cohort were examined at baseline (2007 to 2012) and follow-up five years later (2012 to 2017) to investigative the association between noise annoyance due to multiple sources and prevalent and incident atrial fibrillation. After multivariable adjustment, the results from logistic regression analyses revealed overall consistent and positive associations between noise annoyance and prevalent and incident atrial fibrillation in men, whereas this association was weaker in women, in particular with respect to incident atrial fibrillation. For instance, industrial noise annoyance was associated with 21% (95% confidence interval (CI) 9%-34%) and 18% (8%-29%) higher odds of prevalent atrial fibrillation in men and women, respectively. In prospective analysis, this association remained stable in men (odds ratio (OR) 1.25, 1.07-1.44), while in women no association was observed (OR 1.03, 0.89-1.18). Conclusions: The findings suggest that noise annoyance can increase the risk of incident atrial fibrillation in a large population-based cohort and that men may be more sensitive to the adverse effects of noise annoyance with regard to the risk of atrial fibrillation.